STUDI KOMPARATIF PENAMBAHAN BERAT BADAN BAYI UMUR 0-6 BULAN YANG DIBERI MP-ASI DAN TANPA DIBERI MP-ASI - Dintansari, Esa Oksila; Anasari, Tri; Fridayanti, Warni (Bidan Prada: Jurnal Publikasi Kebidanan Akbid YLPP Purwokerto, 2010)
Giving Mother's Milk (ASI) and complementary feeding (MP-ASI), which appropriately is the best provision for a baby to ensure optimal growth process. To find one infant growth can be seen by monitoring the baby's weight gain. To know the difference adding weight babies fed breast milk and baby-MP without MP-ASI given. This study is a retrospective descriptive comparative approach. The study population were infants aged 6-12 months were 72 people in the Village District Kutasari Kutasari Purbalingga. 51 samples taken by sampling techniques using purposive sampling technique. Methods of data analysis in this study using an independent t-test. Addition of average weight infants in the group of babies fed on MP-ASI at 3858.53 grams. Addition of average weight infants in the group of infants without a MP-ASI at 4800.00 grams. There are differences in weight gain 0-6 months old babies fed on breast milk and without the MP-MP-ASI (p = 0.002). There are differences in weight gain, babies fed breast milk and baby-MP without MP-ASI given. Â  Keywords : MP-ASI, Weight Loss, Infants Aged 6-12 months.